The Becton Dickinson Barricor Tube Does Not Introduce Isobaric Interferences in Mass Spectrometry-based Measurements of Testosterone. (15th October 2019) - Mazur, Chase; Hayden, Joshua
Abstract: Background: Testosterone analysis by mass spectrometry is essential for accurate low-level results. Unfortunately, the commonly used gel-based separator tubes introduce an intense, isobaric interference that can coelute with testosterone and impede analysis. The new Becton Dickinson (BD) Barricor TM tube (BT) uses an elastomer separator that might not introduce such interferences. Methods: Testosterone concentrations and chromatograms were obtained for plasma samples from plasma separator tubes (PSTs) and the new BTs using a laboratory-developed liquid chromatography–tandem mass spectrometry (LC-MS/MS) method. Results: Intense signals close to the testosterone retention time were observed in the testosterone quantifier transition (289.2→97.0) from the PSTs; resolving these signals required longer chromatographic run times. No isobaric interferences were introduced by the BTs, allowing for shorter chromatographic run times and faster inject-to-inject times. Conclusion: BTs do not introduce the interferences observed in PSTs in LC-MS/MS testosterone analysis. These tubes can be used as a single tube that both separates cells and is amenable to LC-MS/MS testosterone analysis without additional chromatographic run times.